49.6k views
0 votes
Solve using elimination....
8x - 3y = -6
-8x + 7y = -18
( ___ , ___ )

User Deeko
by
5.5k points

1 Answer

6 votes

Answer:

x= -3

y= -6

Explanation:

8x - 3y= -6 .........equation 1

-8y + 7y= -18..........equation 2

Using elumination method

Multiply equation 1 by -8 and multiply equation 2 by 8

-64x + 24y = 48

-

64x + 56y =-144

-32y = 192

y = 192/-32

y= -6

Substitute -6 for y in equation 1

8x - 3(-6) = -6

8x + 18= -6

8x= -6 -18

8x=-24

x= -24/8

x= -3

Hence x = -3 and y = -6

User Nikola Benes
by
5.1k points